Aggregation in networks - Nizar Allouch (University of Kent, School of Economics, 2017)
In this paper, we show that a concept of aggregation can hold in network games. Breaking up large networks into smaller pieces, which can be replaced by representative players, leads to a coarse-grained description of strategic interactions. This method of summarizing complex strategic interactions by simple ones can be applied to compute Nash equilibria. We also provide an application to public goods in networks to show the usefulness of our results. In particular, we highlight network architectures that cannot prevent free-riding in public good network games. Finally, we show that aggregation enhances the stability of a Nash equilibrium
Keywords: C72; D31; D85; H41; 330; aggregation; modular decomposition; network games; public goods; stability